PtdIns3P and Rac direct the assembly of the NADPH oxidase on a novel, pre-phagosomal compartment during FcR-mediated phagocytosis in primary mouse neutrophils - Anderson, Karen E. (American Society of Hematology, 2010)
The generation of reactive oxygen species (ROS) by the nicotinamide adenine dinucleotide phosphate oxidase is an important mechanism by which neutrophils kill pathogens. The oxidase is composed of a membrane-bound cytochrome and 4 soluble proteins (p67(phox), p40(phox), p47(phox), and GTP-Rac). These components form an active complex at the correct time and subcellular location through a series of incompletely understood mutual interactions, regulated, in part, by GTP/GDP exchange on Rac, protein phosphorylation, and binding to lipid messengers. We have used a variety of assays to follow the spatiotemporal assembly of the oxidase in genetically engineered primary mouse neutrophils, during phagocytosis of both serum- and immunoglobulin G-opsonized targets. The oxidase assembles directly on serum-Staphylococcus aureus–containing phagosomes within seconds of phagosome formation; this process is only partially dependent (∼ 30%) on PtdIns3P binding to p40(phox), but totally dependent on Rac1/2 binding to p67(phox). In contrast, in response to immunoglobulin G-targets, the oxidase first assembles on a tubulovesicular compartment that develops at sites of granule fusion to the base of the emerging phagosome; oxidase assembly and activation is highly dependent on both PtdIns3P-p40(phox) and Rac2-p67(phox) interactions and delivery to the phagosome is regulated by Rab27a. These results define a novel pathway for oxidase assembly downstream of FcR-activation.